2015
DOI: 10.1080/11745398.2015.1007881
|View full text |Cite
|
Sign up to set email alerts
|

Towards a model of optimal family leisure

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
0
9
0
4
Order By: Relevance
“…Щоб мобілізувати та використовувати інші сімейні ресурси, потрібен час. Серед різноманітних моделей використання сімейного часу є чимало доказів позитивного зв'язку між участю в сімейному дозвіллі та сімейним функціонуванням [3,4,7,10,21]. Потрібне повне розуміння потенційного впливу участі батьків у ОРРА дітей.…”
Section: науковий часопис нпу імені м п драгоманова випуск 8 (153) 20...unclassified
See 1 more Smart Citation
“…Щоб мобілізувати та використовувати інші сімейні ресурси, потрібен час. Серед різноманітних моделей використання сімейного часу є чимало доказів позитивного зв'язку між участю в сімейному дозвіллі та сімейним функціонуванням [3,4,7,10,21]. Потрібне повне розуміння потенційного впливу участі батьків у ОРРА дітей.…”
Section: науковий часопис нпу імені м п драгоманова випуск 8 (153) 20...unclassified
“…Як Keri A. Schwab та ін. [21] припускають, що сильні та важливі мотиви для участі в ОРРА відрізняються залежно від видів діяльності, віку та статі дорослих. Систематичний огляд Пасічняк Л. та Дудчак М [13] також надає хороші докази цінності особистості для розуміння поведінки під час фізичних вправ, демонструючи важливість автономної (ідентифікованої та внутрішньої) регуляції у сприянні ОРРА.…”
Section: науковий часопис нпу імені м п драгоманова випуск 8 (153) 20...unclassified
“…A couple's relationship can deteriorate gradually when there is a lack of order and predictability, a phenomenon referred to as entropy. For decades, family and leisure scholars have suggested that couples should spend their time together in rituals, routines, and recreation to provide predictable, regular interactions that enhance couples' relationships (e.g., Doherty, ; Fiese, ; Orthner, ; Schwab & Dustin, ; Zabriskie & McCormick, ). Scholars from these fields describe the positive association between family leisure activities and family bonding (Fiese, ; Hodge et al, , Orthner & Mancini, 1990; Townsend, Van Puymbroeck, & Zabriskie, ; Zabriskie & McCormick, ); yet no studies from these fields have examined the underlying mechanisms of family leisure activities that produce family bonding.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The most negative manifestations in this regard include the formation of personality which is sometimes characterized by greed, thus driving the translation of all values into material goods with the focus on raising the standards of living. This not only leads to impoverishment of the content and forms of leisure time, but also to its excessive reduction and sometimes even to the complete abandonment of leisure time in the family [2,15,25,38,30,43,44]. One also needs to mention here the issue of new technology.…”
Section: Introductionmentioning
confidence: 99%